Multimodal analysis of Instagram content: The involvement of candidates' wives in the 2024 Indonesian election Campaign - Olivia, Meydisah; Yuniar, Ririt (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
In political contestation, the involvement of candidate spouses in campaigns is becoming an increasingly prominent phenomenon. The participation of candidate wives in political campaigns is not just a companion, but an important strategy in gaining voter support in the 2024 Election. Campaigning is a political strategy to gain public support to achieve political victory. In the 2024 Election process in Indonesia, several candidate wives were actively involved in political campaign events. This study analyzes how political candidate wives describe their roles and involvement in the campaign process through social media. Using Kress and Van Leeuwen's multimodal concept analysis with a qualitative approach, data collection through content in the form of videos and photos, focusing on campaign activities carried out by Fery Farhati, Anies Baswedan's wife, and Siti Atikoh, Ganjar Pranowo's wife, then analyzed using qualitative descriptive analysis techniques. The results first found that the candidate's wife was represented as an active and caring figure through social involvement; Second, the use of visuals in the content plays a role in building the candidate's wife's closeness to the audience; Third, the composition of the image can emphasize their role in the campaign. In conclusion, political candidates' wives in campaigns are often used to build a positive image of political candidates and strengthen political messages by displaying a humanistic side that can attract public sympathy.